A RESEARCH-BASED APPROACH TO THE USE OF TEXT AND DISCOURSE IN EDUCATIONAL SYSTEMS - Asranov Sodik Aminzhonovich (Bright Mind Publishing, 2025)
This article explores a research-oriented approach to integrating text and discourse analysis into modern educational systems. Drawing on concepts from linguistics, discourse studies, pedagogy, and cognitive science, it examines how textual practices shape learning processes, identity formation, and critical literacy. The paper outlines theoretical foundations, methodological tools, and practical applications of discourse-centered pedagogy in primary, secondary, and higher education. It argues that a research-based approach to text and discourse helps create reflective, participatory, and critically engaged learning environments. The article concludes with suggestions for incorporating discourse analysis into curriculum design, teacher training, and assessment practices.
Keywords: Text analysis, discourse, educational system, critical literacy, pedagogy, research-based approach, language practices, discourse analysis